Investigation of an Ultra-Wideband Optical Absorber with the Bandwidth from Ultraviolet C to Middle Infrared - Chih-Ching Hung; Xin-Yu Lin; Tung-Lung Wu; Shu-Han Liao; Ho-Sheng Chen; Cheng-Fu Yang (Photonics, 2025)
In the development of optical absorption technology, achieving ultra-wideband high absorption structures that span from the 200 nm ultraviolet C region to the 5800 nm mid-infrared range has been a significant challenge in materials science. Previous studies have shown that few optical absorbers can simultaneously achieve an absorption rate above 0.900 and cover such a vast spectral range. This study presents an innovative seven-layer composite structure that successfully addresses this long-standing technical issue. Through a carefully designed layered architecture, the researchers employed COMSOL Multiphysics (version 6.0) for detailed numerical simulations to verify the optical performance of the structure. The structural design features two key innovations. In the layered composition, the bottom (h1), h3, and h5 layers are made of metallic Fe, while the layers above them (h2, h4, and h6) use SiO2. The top layer is composed of a discontinuous cylinder Ti matrix. The first innovation involves the use of an inwardly recessed square design on the metallic Fe planes of the h4 and h6 layers, achieving high absorption across the 600–5800 nm range. The second innovation involves the use of the discontinuous cylinder Ti matrix for the top layer, which successfully enhances absorption performance in the 200–600 nm wavelength range. This structure not only employs relatively low-cost metals and oxide materials but also demonstrates significant optical absorption potential. Through numerical simulations and precise structural design, this study provides new ideas and technological pathways for the development of ultra-wideband optical absorbers.